Causes, temporal trends, and the effects of urbanization on admissions of wild raptors to rehabilitation centers in England and Wales. Issue 4 (20th April 2022) - Panter, Connor T.; Allen, Simon; Backhouse, Nikki; Mullineaux, Elizabeth; Rose, Carole‐Ann; Amar, Arjun
Abstract: Data from wildlife rehabilitation centers (WRCs) can provide on‐the‐ground records of causes of raptor morbidity and mortality, allowing threat patterns to be explored throughout time and space. We provide an overview of native raptor admissions to four WRCs in England and Wales, quantifying the main causes of morbidity and mortality, trends over time, and associations between threats and urbanization between 2001 and 2019. Throughout the study period, 14 raptor species were admitted totalling 3305 admission records. The Common Buzzard ( Buteo buteo ; 31%) and Tawny Owl ( Strix aluco ; 29%) were most numerous. Relative to the proportion of breeding individuals in Britain and Ireland, Peregrine Falcons ( Falco peregrinus ), Little Owls ( Athene noctua ), and Western Barn Owls ( Tyto alba ) were over‐represented in the admissions data by 103%, 73%, and 69%, respectively. Contrastingly Northern Long‐eared Owls ( Asio otus ), Western Marsh Harriers ( Circus aeruginosus ), and Merlin ( Falco columbarius ) were under‐represented by 187%, 163%, and 126%, respectively. Across all species, vehicle collisions were the most frequent anthropogenic admission cause (22%), and orphaned young birds (10%) were most frequent natural cause. Mortality rate was highest for infection/parasite admissions (90%), whereas orphaned birds experienced lowest mortality rates (16%). For one WRC, there was a decline in admissions over the study period. Red Kite ( Milvus milvus ) admissions increased over time, whereas Common Buzzard and Common Kestrel admissions declined. There were significant declines in the relative proportion of persecution and metabolic admissions and an increase in orphaned birds. Urban areas were positively associated with persecution, building collisions, and unknown trauma admissions, whereas vehicle collisions were associated with more rural areas. Many threats persist for raptors in England and Wales, however, have not changed substantially over the past two decades. Threats associated with urban areas, such as building collisions, may increase over time in line with human population growth and subsequent urban expansion. Abstract : We provide an overview of native raptor admissions to four WRCs in England and Wales. Vehicle collisions and orphaned birds were the most frequently identified causes of admission. Urban areas were positively associated with persecution, building collisions, and unknown trauma, whereas vehicle collisions were associated with more rural areas.